ChemInform Abstract: Crystal Growth of New Hexahydroxometallates Using a Hydroflux. Issue 1 (7th January 2014) - Chance, W. Michael; Bugaris, Daniel E.; Sefat, Athena S.; zur Loye, Hans‐Conrad
Abstract Single crystals of the new compounds Sr2Mn(OH)6, Ba2Mn(OH)6, Sr2Co(OH)6, Ba2Co(OH)6, Sr2Ni(OH)6, Ba2Ni(OH)6, and Ba2Cu(OH)6 are prepared from M(OH)2 (M: Sr, Ba) and MnCl2, CoCl2, Ni(NO3)2, or CuO using a combination of water with NaOH, KOH, or a NaOH/KOH mixture as hydroflux (180—230 °C, 12—36 h).